If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -3 = 2x + 21 Reorder the terms: -3 + 6x = 2x + 21 Reorder the terms: -3 + 6x = 21 + 2x Solving -3 + 6x = 21 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -3 + 6x + -2x = 21 + 2x + -2x Combine like terms: 6x + -2x = 4x -3 + 4x = 21 + 2x + -2x Combine like terms: 2x + -2x = 0 -3 + 4x = 21 + 0 -3 + 4x = 21 Add '3' to each side of the equation. -3 + 3 + 4x = 21 + 3 Combine like terms: -3 + 3 = 0 0 + 4x = 21 + 3 4x = 21 + 3 Combine like terms: 21 + 3 = 24 4x = 24 Divide each side by '4'. x = 6 Simplifying x = 6
| y=0.0003x+2.7614 | | F=7/5(n-7) | | 2x+(-4)=y | | 7-4x+3=1x-16-3x | | x/33=4 | | ((3x^2y^3)^3)/(27(xy)^-9) | | x+108.76=177.18 | | -4+2x+10=22+2x | | f(x)=-x^2+1.8x+2.5 | | -3x+5=-14 | | (3x^2y^3)^3/27(xy)^-9 | | 2(X)-3=4(x-1)-1-2x | | (3x^2y^3)^2/27(xy)^-9 | | f(x)=(-x^2)+(1.8x)+(2.5) | | x^2+4y^2+24y=0 | | 7-(7x+5)=13+3x | | v/2-8=22 | | 9x-25=5x-7 | | -14=-4+5v | | 5x=x-1 | | 31x=440.20 | | -6e^8x+8-3=-23 | | X-8/x^2-36 | | -16.2h=-14.67-17.1h | | 7/9x-7 | | 8(x+3)-12=2x | | 12x-3=21+3 | | 6=210-3x | | 349+x=532.93 | | 5x+5+13x-5=180 | | 2/(x-5)-1/(x-5)=11/(x-25) | | x^2-12x-9564=0 |